Structural unemployment and the output gap in Germany : evidence from an SVAR analysis within a hysteresis framework - Ulrich Fritsche; Camille Logeay (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
The German unemployment rate shows strong signs if non-stationarity over the course of the previous decades. This is in line with an insider-outsider model under full hysteresis. We applied a "theory-guided view" to the data using the structural VAR model as developed by Balmaseda, Dolado and López-Salido (2000) allowing for full hysteresis on the labour market. Our identification of the model implies long-lasting output gaps for Germany – especially for the disinflation period of the 1980s.
Keywords: C32; J64; E32; E12; 330; Structural unemployment; output gap; structural VAR; insider-outsider model; Strukturelle Arbeitslosigkeit; Konjunktur; Kapazitätsauslastung; Arbeitsmarkt; Insider-Outsider-Modell; VAR-Modell; Schätzung; Deutschland